The State of Social Infrastructure in Rural Areas of Katsina State, Northern Nigeria - Garba, Abdullahi (NIU Journal of Humanities, 2017)
Social infrastructure support sustained both social and economic growth and improved quality and living conditions of the community.  Social infrastructures remain the core element of rural welfare.  Thus efforts to  raise  rural  welfare  must   necessarily  go  beyond the  traditional and limited approved of raising per capita income through agricultural development projects to the provision of  rural basic needs  in term of  health and medical  facilities, potable water  and   schools .  The objective of the research study was to assess the state of social infrastructure (health facilities in particular) in rural areas of Katsina State, Northern Nigeria.  The methodology employed by the research is triangulation method in which quantitative and qualitative instruments were used.  Data collected was mainly based on primary and secondary sources.  The findings of the research study indicate that social infrastructure has an overall average mean of (2.4531) which is low on Likert scale.  Social infrastructure (health facilities in particular) in Katsina state, Northern Nigeria is ironically meagre and efforts made to improve them have not yielded desired results.  Some of the recommendations of the research study include increase in funding by the government, donor organization and nongovernmental organizations, involvement of the rural populace in the decision making, involvement of the populace in the provision of social infrastructures itself in rural Katsina state, Northern Nigeria. Keywords: Rural Areas, Social Infrastructure.